1981
DOI: 10.1203/00006450-198103000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Immaturity of the ADH-Dependent cAMP System in Conscious Newborn Piglets—Possible Impairing Effects of Renal Prostaglandins

Abstract: SummaryIn 24 conscious newborn piglets the effects of 20 &kg body weight IV 1-deamino-&~-arginine-vasopressin (DDAVP) in group 1, 5 mg/kg P O indomethacin in group 2, and the combined effects of both drugs in group 3 were studied by measuring urinary flow rate. urinary osmolality, creatinine clearance, total urinary and nephrogenols cyclic-adknosine 3':s'-monophosphate (CAMP) excretion. medullary cAMP content. and renal prostaglandin (PG)E2 and PGF2,, excreiion. DDAVP alone had no-signifilcant effects on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…In support of this con cept Joppich et al [ 11 ] observed that in new born piglets DDAVP administration alone had no significant effect on urinary cAMP excretion and urine osmolality whereas DDAVP given with indomethacin resulted in a significant increase in medullary cAMP content, urinary cAMP excretion and urine osmolality.…”
Section: End-organ Responsiveness To a Vpsupporting
confidence: 51%
“…In support of this con cept Joppich et al [ 11 ] observed that in new born piglets DDAVP administration alone had no significant effect on urinary cAMP excretion and urine osmolality whereas DDAVP given with indomethacin resulted in a significant increase in medullary cAMP content, urinary cAMP excretion and urine osmolality.…”
Section: End-organ Responsiveness To a Vpsupporting
confidence: 51%
“…A progressive decline in urinary concentration of PGE 2 during ontogenesis is accompanied by an increase in urine osmolality [13]. Moreover, studies on newborn piglets have shown that administration of indomethacin leads to increased urine osmolality and urinary cAMP levels [14], suggesting that prostaglandins mediate the hyposthenuria of the immature kidney. In contrast, our results showed that despite inhibition of endogenous prostaglandin production by indomethacin, the AVP-stimulated water permeability in the iCCD remained significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of prostaglandins have been found in urine from fetal lambs and preterm human infants [8,13]. Furthermore, inhibition of endogenous prostaglandin synthesis by indomethacin increases urinary osmolality and nephrogenous cAMP excretion in newborn piglets, suggesting that the renal resistane to AVP could be mediated by prostaglandins [14].…”
Section: Introductionmentioning
confidence: 99%
“…prostaglandin E? (35). Such an antagonist might explain the uncommon occurrence of the syndrome of inappropriate antidiuretic hormone in sick neonates despite high levels of AVP secretion.…”
Section: Discussionmentioning
confidence: 99%